Predictive Validity of Kindergarten Progress Monitoring Measures Across the School Year: Application of Dominance Analysis. (September 2019) - Clemens, Nathan H.; Hsiao, Yu-Yu; Simmons, Leslie E.; Kwok, Oi-man; Greene, Emily A.; Soohoo, Michelle M.; Henri, Maria A.; Luo, Wen; Prickett, Christopher; Rivas, Brenna; Otaiba, Stephanie Al
Although several measures are available for monitoring kindergarten reading progress, little research has directly compared them to determine which are superior in predicting year-end reading skills relative to other measures, and how validity may change across the school year as reading skills develop. A sample of 426 kindergarten students who were considered to be at risk for reading difficulty at the start of kindergarten were monitored across the year with a set of paper-based progress monitoring measures and a computer-adaptive test. Dominance analyses were used to determine the extent to which each measure uniquely predicted year-end reading skills relative to other measures. Although the computer-adaptive test was the most dominant predictor at the start of the year over letter sound fluency, letter naming fluency, and phoneme segmentation fluency, letter sound fluency was most dominant by December. Measures of fluency reading real words administered across the second half of the year were dominant to all other assessments. The implications for measure selection are discussed.